In Situ Imaging of Ion Motion in a Single Nanoparticle: Structural Transformations in Selenium Nanoparticles. (23rd September 2022) - Chen, Bin Bin; Liu, Meng Li; Zou, Hong Yan; Liu, Yang; Li, Yuan Fang; Swihart, Mark T; Huang, Cheng Zhi
Abstract: Intraparticle ion motions are critical to the structure and properties of nanomaterials, but rarely disclosed. Herein, in situ visualization of ion motions in a single nanoparticle is presented by dark‐field microscopy imaging, which shows HgCl2 ‐induced structural transformation of amorphous selenium nanoparticles (SeNPs) with the main composition of Se8 . Owing to the high binding affinity with selenium and coulomb interactions, Hg 2+ ions can permeate into the interior of SeNPs, making the amorphous Se8 turn to polycrystalline Hg3 Se2 Cl2 . As a proof of concept, SeNPs then serve as a highly effective scavenger for selective removal of Hg 2+ ions from solution. This new finding offers visual proof for the photophysical process involving intraparticle ion motion, demonstrating that tracking the ion motions is a novel strategy to comprehend the formation mechanism with the purpose of developing new nanostructures like nanoalloys and nano metal compounds. Abstract : In situ and real‐time visualization of ion motions in a single nanoparticle was achieved by dark‐field microscopy and disclosed the transformation of amorphous SeNPs into polycrystalline Hg3 Se2 Cl2 .